2011
DOI: 10.1021/nl203457v
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Photosensitization of a Wide Band Gap Semiconductor: Converting Plasmons to Charge Carriers

Abstract: A fruitful paradigm in the development of low-cost and efficient photovoltaics is to dope or otherwise photosensitize wide band gap semiconductors in order to improve their light harvesting ability for light with sub-band-gap photon energies.(1-8) Here, we report significant photosensitization of TiO2 due to the direct injection by quantum tunneling of hot electrons produced in the decay of localized surface-plasmon polaritons excited in gold nanoparticles (AuNPs) embedded in the semiconductor (TiO2). Surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
336
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(346 citation statements)
references
References 35 publications
7
336
0
3
Order By: Relevance
“…First, Tatsuma et al [37,38,45] and other workers [42,46] proposed that the photoexcited electrons in the metal nanoparticles transferred from the metal particle to the TiO2 conduction band since the photoresponse of these metal-TiO2 diode structures was consistent with the absorption spectra of Au or Ag nanoparticles. Second, Kamat et al [43,44] and Li et al [47] have suggested that the noble metal nanoparticles act as electron sinks or traps in the metal-TiO2 diode structures to accumulate the photogenerated electrons, which could minimize charge recombination in the semiconductor films.…”
Section: Review Of Metal-insulator-metal (Mim) Diodesmentioning
confidence: 94%
See 2 more Smart Citations
“…First, Tatsuma et al [37,38,45] and other workers [42,46] proposed that the photoexcited electrons in the metal nanoparticles transferred from the metal particle to the TiO2 conduction band since the photoresponse of these metal-TiO2 diode structures was consistent with the absorption spectra of Au or Ag nanoparticles. Second, Kamat et al [43,44] and Li et al [47] have suggested that the noble metal nanoparticles act as electron sinks or traps in the metal-TiO2 diode structures to accumulate the photogenerated electrons, which could minimize charge recombination in the semiconductor films.…”
Section: Review Of Metal-insulator-metal (Mim) Diodesmentioning
confidence: 94%
“…However, in these recent metal-TiO2 Schottky diode structures [37][38][39][40][41][42][43][44][45][46][47], it would appear that the barrier layer was actually quite a bit thicker than 10 nm (probably in excess of 1 um) and further details was unable to be found in these papers. Semi-classical models did not account for non-equilibrium energy distributions of carriers, or do so through a localize lattice temperature.…”
Section: Theoretical Modeling Of Ag-tio2-ti Mim Diodesmentioning
confidence: 98%
See 1 more Smart Citation
“…A spectroscopic transition, which normally takes place in the UV, can in this case be excited by visible light 35 . The electron has sufficient energy to cross the space charge layer 105,106 , resulting in a significant photocurrent 107,108 . The hole remaining in the metal close to the Fermi level assists the mechanistically complex oxidation reactions at the Au surface, with the reduction reactions possibly driven unconventionally at the semiconductor 109 .…”
Section: Supplementary Led Illuminationmentioning
confidence: 99%
“…Due to the strongly enhanced EM field at the nanowire gaps, this system were also used in plasmonic catalysis, such as water splitting and the reaction of PATP to DMAB 94, 95, 96. In this remote sensing system, the silver nanowire array was used as a probe, which can be attached to a catheter or an optical fiber to collect remote SERS signals in biological cell or liquids 55.…”
Section: Plasmonic Waveguide For Remote‐excitationmentioning
confidence: 99%